2012
DOI: 10.1155/2012/839053
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Technology for High‐Throughput Screening of Interactions between Cells and Nanostructured Materials

Abstract: We present a novel substrate suitable for the high-throughput analysis of cell response to variations in surface chemistry and nanotopography. Electrochemical etching was used to produce silicon wafers with nanopores between 10 and 100 nm in diameter. Over this substrate and flat silicon wafers, a gradient film ranging from hydrocarbon to carboxylic acid plasma polymer was deposited, with the concentration of surface carboxylic acid groups varying between 0.7 and 3% as measured by XPS. MG63 osteoblast-like cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…The spectrum was fitted with five components for CÀH/CÀC (285.0 eV;5 1.9 %, Figure 3b ). [18,21] Overall,t he results the XPS measurements corroborate the ATR-FTIR measurements and taken together, both XPS and ATR-FTIR not only confirmed that the plasma polymer films formed ac ontinuous layer across the pSi surface,b ut also indicateg ood retention of the carboxylic acid functionality from the PAAc film.…”
Section: Sem Images Insupporting
confidence: 67%
See 1 more Smart Citation
“…The spectrum was fitted with five components for CÀH/CÀC (285.0 eV;5 1.9 %, Figure 3b ). [18,21] Overall,t he results the XPS measurements corroborate the ATR-FTIR measurements and taken together, both XPS and ATR-FTIR not only confirmed that the plasma polymer films formed ac ontinuous layer across the pSi surface,b ut also indicateg ood retention of the carboxylic acid functionality from the PAAc film.…”
Section: Sem Images Insupporting
confidence: 67%
“…The C 1s peak of the pSi‐POct‐PAAc surface in Figure b shows the expected spectral feature for PAAc. The spectrum was fitted with five components for C−H/C−C (285.0 eV; 51.9 %, Figure b (i)), C‐Y(=O)OX (285.4 eV; 11.3 %; Figure b (ii)), Y−C(=O)OX (289.1 eV; 11.3 %; Figure b (iii)), C−O (286.5 eV; 14.8 %; Figure b (iv)) and C=O (287.7 eV; 7.4 %; Figure b (v)) . Overall, the results the XPS measurements corroborate the ATR‐FTIR measurements and taken together, both XPS and ATR‐FTIR not only confirmed that the plasma polymer films formed a continuous layer across the pSi surface, but also indicate good retention of the carboxylic acid functionality from the PAAc film.…”
Section: Resultsmentioning
confidence: 96%
“…More recently, the ability of plasma polymers to retain chemical functionality has been exploited to fabricate non‐fouling surfaces, graft polymer brushes to surfaces, and attach biomolecules to surfaces in order to improve biocompatibility and cell adhesion . Indeed functionalized plasma polymers have found application in a wide variety of areas, including coatings on fibers, improving interfacial adhesion in composite materials, for cell attachment and screening, nanoparticle attachment, biosensors, and as membranes for fuel cells …”
Section: Introductionmentioning
confidence: 99%
“…Physiological and pathological processes are often driven by gradients of biological signals and a number of studies have shown that disaggregated individual cells sense and respond to gradients of properties on a solid material such as a slide or a tissue culture well. [25][26][27][28][29][30][31][32][33] Numerous physiological processes such as tissue development and diseases are also driven by gradients of biological signals. [34][35][36][37][38] Chemical gradients drive processes such as immune response, neovascularization, and stem cell differentiation.…”
Section: Introductionmentioning
confidence: 99%